Implementation of ChatGPT Artificial Intelligence in Learning - Gabriela Nicola; Jackson, Stuart; Queen, Zabenaso (Blockchain Frontier Technology, 2024)
Learning media is a means that can improve the quality and provide convenience in teaching and learning activities for teaching staff and students. One form of technology-based learning media that is widely used is ChatGPT (Generative Pre-Training Transformer), an artificial intelligence system that allows conversational interaction via text. ChatGPT has the ability to respond to human questions written in the application. Its functions include helping students understand complex subject matter, addressing gaps in understanding, and increasing learning effectiveness. Its appeal to teachers and students lies in its structured answers and ability to solve problems quickly. This research uses the literature study method, an approach that involves in-depth analysis of literature or references. The focus of this research is to review the implementation of ChatGPT in learning, starting from the procedures for using the application, advantages and disadvantages, to the use of prompts so that teachers and students can utilize this media effectively. Therefore, it is hoped that this research can provide answers regarding relevance, more accurate information, and guidelines for using ChatGPT in a learning context. The importance of integrating technology in learning with an appropriate and effective approach, as well as developing competence for teachers in managing technology-based learning, is an important point in this context